First description of the male of Sphecotypus niger (Perty, 1833), with notes on behavioral and morphological mimicry (Araneae: Corinnidae: Castianeirinae) - Leister, Matthew; Miller, Kelly (Zootaxa, 2014)
The genus Sphecotypus O. Pickard-Cambridge, 1895, is currently represented by three species: S. birmanicus (Thorell, 1897) from Myanmar and Borneo, S. taprobanicus Simon, 1897 from Sri Lanka, and S. niger (Perty, 1833) from Central and South America. Of the three currently known species, only S. birmanicus has both sexes described, whereas the other two species are known from female specimens only, including the type species of the genus, S. niger (Deeleman-Reinhold 2001). Material recently examined from Costa Rica and Nicaragua included several specimens, including a male of S. niger, which is described here. The northern-most documented distribution of S. niger was Panama (Reiskind 1969; Platnick 2014). Thus, the specimens from Nicaragua extend the known range of these spiders further north.